Industries without smokestacks: Mozambique country case study - Antonio S. Cruz; Fausto J. Mafambissa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Under the current international economic conditions, where Asian countries are strong competitors in the manufacturing commodities, low-income countries like Mozambique could attempt to compete in industries without smokestacks. Fruits and vegetables, agro-processing goods, and various tradable services are estimated to have contributed 1.9 per cent to annual average gross domestic product growth in 1993-2015, when the aggregate growth was 7.8 per cent. Around 80 per cent of the total labour force is dedicated to primary activities, producing 25 per cent of the aggregated value added in 2013-2015. The share of services in total exports was only 17 per cent in 2012-14. Although still relatively small, these industries have potential for growth, if Mozambique follows a diversified growth strategy.
Keywords: L6; L8; O2; O4; O5; 330; industries; exports; policy; growth strategy; national accounts; Mozambique